THE ISSUE OF DIFFICULTIES FACED BY TWELFTH GRADE STUDENTS IN LEARNING CHEMISTRY ON THE SUBJECT OF ALKYNE DERIVATIVES - Daulay, Rabiah Afifah; Damayanti, Alfina; Shaharani, Adella; Anggriani, Syaprina; Syafitri, Wanda; Nasution, Yara Maulina (Transpublika Publisher, 2023)
Learning difficulties refer to conditions when students face special obstacles in actively participating in the teaching and learning process, resulting in challenges in achieving optimal learning outcomes. One of the specific difficulties students’ encounters is related to understanding the concepts of alkyne derivatives in chemistry. This research aims to explore the problematic difficulties faced by 12th grade students while learning about alkyne derivatives. The study adopts a qualitative approach and relies on a literature review, presenting descriptive findings. Data collection involves analyzing various sources, including scientific articles, theses, proceedings, and books that are relevant to the research focus. The study reveals that student learning difficulties are influenced by two major factors: internal and external. Internal factors include physiological aspects such as physiological conditions and the functioning of the five senses. Psychological factors also play a role, encompassing interests, intelligence, talent, motivation, and cognitive abilities. External factors, on the other hand, comprise social and natural environmental influences, as well as instrumental factors like the curriculum, programs, facilities, infrastructure, and the role of teachers.